2019
DOI: 10.1111/jar.12609
|View full text |Cite
|
Sign up to set email alerts
|

Friendships and patterns of social leisure participation among Norwegian adolescents with Down syndrome

Abstract: Background A first generation of adolescents with Down syndrome have grown up in Norway's inclusive society. This study explored their friendships and social leisure participation, mainly as it is reflected through their subjective experience. Method The analysis is based on qualitative interviews and observations of 22 teens aged 17 years. Results Generally, the adolescents described their social life as rich and varied, occurring in several contexts with different companions. Their thoughts of friendships we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
3
8
0
2
Order By: Relevance
“…These findings support the recent literature which found that communication ability is associated with having a best friend (Dolva et al, 2019), that staff knowing the friendship preferences of those they support increases their chances of having friends (Friedman & Rizzolo, 2018), that staff perceptions and understanding of the individuals they support is important to participation and connecting with others (Kamstra et al, 2019; Talman et al, 2019), and that continuity and familiarity of support staff enhances inclusion (Friedman & Rizzolo, 2018; McCausland et al, 2019). This suggests that better communication support for those with such difficulties is required, including training for staff to better understand, interpret and support people with significant communication difficulties to meet people and to form and maintain friendships.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings support the recent literature which found that communication ability is associated with having a best friend (Dolva et al, 2019), that staff knowing the friendship preferences of those they support increases their chances of having friends (Friedman & Rizzolo, 2018), that staff perceptions and understanding of the individuals they support is important to participation and connecting with others (Kamstra et al, 2019; Talman et al, 2019), and that continuity and familiarity of support staff enhances inclusion (Friedman & Rizzolo, 2018; McCausland et al, 2019). This suggests that better communication support for those with such difficulties is required, including training for staff to better understand, interpret and support people with significant communication difficulties to meet people and to form and maintain friendships.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it was encouraging that the large majority of respondents (92.4%, 560/606) had friends; although just over half of these had a best friend (56.6%, 317/560; or 52% of the full sample (317/609)). This is broadly comparable to rates of friendship found in previous studies (Dolva et al, 2019; Friedman & Rizzolo, 2018). The finding that almost half of respondents did not have a friendship close enough to call a ‘best friend’ may also reflect previous findings of dissatisfaction with existing levels of friends and a desire for more friends (Friedman & Rizzolo, 2018; Robinson et al, 2018), difficulties reported with developing and maintaining friendship (Merrells et al, 2019) and smaller networks including fewer friends than found in the general population (White & Forrester‐Jones, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…También hay otros estudios como el de Rodrigo-Moriche et al ( 2022) que contempla una perspectiva positiva en el ejercicio del ocio y tiempo libre al ser una excelente oportunidad para el desarrollo de competencias digitales desde un entorno educativo informal espontáneo y pleno de placer y disfrute. En este sentido, también se contempla el ocio adolescente en el grupo de iguales desde un enfoque positivo, de modo que se considera un factor esencial para la inclusión, fortalecimiento de las relaciones de amistad y adquisición de patrones de participación social, de aquellos que se encuentran en una situación de necesidad educativa especial (Dolva et al, 2019). Se da, por tanto, una multitud de estudios que hace que exista una diversificación de tipologías de ocio atendiendo a diferentes intereses, una de las más extendidas y generalizadas es la realizada por Cuenca (2000) el cual establece cinco dimensiones que agrupa las diferentes actividades del ocio, estas son:…”
Section: Introductionunclassified